The use of hematopoietic stem cells in autoimmune diseases. (June 2016) - Ben Nasr, Moufida; Bassi, Roberto; Usuelli, Vera; Valderrama-Vasquez, Alessandro; Tezza, Sara; D'Addio, Francesca; Fiorina, Paolo
Hematopoietic stem cells (HSCs) have been shown recently to hold much promise in curing autoimmune diseases. Newly diagnosed Type 1 diabetes individuals have been successfully reverted to normoglycemia by administration of autologous HSCs in association with a nonmyeloablative regimen (antithymocyte globulin + cyclophasmide). Furthermore, recent trials reported positive results by using HSCs in treatment of systemic sclerosis, multiple sclerosis and rheumatoid arthritis as well. Early data suggested that HSCs possess immunological properties that may be harnessed to alleviate the symptoms of individuals with autoimmune disorders and possibly induce remission of autoimmune diseases. Mechanistically, HSCs may facilitate the generation of regulatory T cells, may inhibit the function of autoreactive T-cell function and may reshape the immune system.